Análisis y Diagnóstico Financiero en la Empresa Distribuidora de Combustibles Wayuu S.A.S. con Normas Internacionales de Información Financiera (2021)
The financial diagnosis of a company is of great relevance since through it everything related to the performance and management of the different areas such as directives and operations can be identified. Therefore, with the objective of this review is to compile all the studies raised in relation to the reliability and financial diagnosis of the companies with more in the specific case, it is intended to determine the relationship with the fuel, auto parts and vehicle maintenance sector together In order to determine, based on these studies and / or articles, the analysis extracted and the financial projections that contribute to provide support to establish the viability of the financial diagnosis of the fuel distribution company Wayuu SAS, which has a main address in the city of Maicao. La Guajira and in the development of its social objective is dedicated to the wholesale trade of solid, liquid and gaseous fuels. For this reason, it is necessary to highlight that within the objectives of said company it is relevant to Identify and face needs such as: the analysis of the financial situation and diagnosis of the financial situation of the same. Therefore, in order to respond to these needs, with this investigation the current status of the fuel distribution company Wayuu S.A.S. will be revealed. Lisandro's financial diagnosis.